Role of Ethnicity in Alignment Compensation: Propensity Matched Analysis of Differential Compensatory Mechanism Recruitment Patterns for Sagittal Malalignment in 288 ASD Patients From Japan, Korea, and United States. Issue 4 (15th February 2017) - Diebo, Bassel G.; Gammal, Isaac; Ha, Yoon; Yoon, Seung Hwan; Chang, Jae won; Kim, Byeongwoo; Matsumoto, Morio; Yamato, Yu; Takeuchi, Daisaku; Hosogane, Naobumi; Yagi, Mitsuru; Taneichi, Hiroshi; et al.
Abstract : Study Design: Retrospective review of adult spinal deformity patients in a multiethnic database. Objective: To investigate the role of ethnicity on recruitment of compensatory mechanisms for sagittal spinal deformity. Summary of Background Data: While the impacts of age, sex, and pelvic morphology on the ability to compensate for sagittal malalignment have been investigated, the role of ethnicity in compensatory mechanism recruitment is poorly understood. Methods: Patients from USA (85% Caucasian) >25 y/o were propensity matched by age, sex, and pelvic incidence with patients from Korea and Japan. Only primary patients or those with existing fusion below T12 were retained for analysis. Groups were subclassified by deformity severity (aligned: sagittal vertical axis (SVA) <50 mm; moderate malalignment: SVA 50–100 mm; severe malalignment: SVA >100 mm). Radiographic measurements including pelvic retroversion, thoracic kyphosis, loss of lumbar lordosis (PI minus LL), cervical lordosis, and cervical SVA were compared between the groups. Results: There were 288 patients (96 each in USA, KOR, JPN), with similar age (64–67 yr) and PI (49–53°). USA had smaller pelvic incidence minus lumbar lordosis in every alignment group ( P <0.05). In moderate malalignment, JPN had more pelvic retroversion than USA (30° vs. 20°), and KOR had more thoracic hypokyphosis than USA (15 vs. 31°). In severe malalignment, JPN had more pelvic retroversion than USA (39° vs . 27°), and KOR had more thoracic hypokyphosis than USA (15° vs. 31°). KOR had smaller cSVA than USA in both aligned (11 vs. 27 mm) and moderate (19 vs. 31 mm) malalignment. In severe malalignment, KOR had less cervical lordosis (13° KOR vs . 15° USA vs . 27° JPN). All differences with P <0.05. Conclusion: Compensation for sagittal is ethnicity dependent. Korean patients favor thoracic compensation via hypokyphosis, and Japanese patients favor pelvic compensation via retroversion. Patient ethnicity should be considered when evaluating the sagittal plane and surgical correction strategies. Level of Evidence: 3